2005
DOI: 10.1007/s10194-005-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of a GH–producing pituitary adenoma associated with a unilateral headache with autonomic signs

Abstract: IntroductionTen to fifteen percent of all diagnosed cerebral tumours are pituitary adenomas (60%-70% are secreting adenomas) that frequently occur during the 3rd or 4th decades of life. Half of them are diagnosed early by clinical hormonal symptoms even when the dimensions of the adenomas are small (5 mm) and the tumours are undetected on magnetic resonance imaging (MRI) scans. Among these, however, growth hormone (GH)-producing macroadenomas are uncommon, and often have blood hormonal levels so low that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Nonetheless, neither systemic parameters such as medical therapy and hormonal hypersecretion (significant effect only on painDETECT score) had significant impact on pain, suggesting previous irreversible effects on the CNS leading to chronic pain. This contradicts previous findings, especially in patients with prolactinoma and acromegaly, showing positive correlation between headache and circulating PRL levels or GH excess respectively (35,36).…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, neither systemic parameters such as medical therapy and hormonal hypersecretion (significant effect only on painDETECT score) had significant impact on pain, suggesting previous irreversible effects on the CNS leading to chronic pain. This contradicts previous findings, especially in patients with prolactinoma and acromegaly, showing positive correlation between headache and circulating PRL levels or GH excess respectively (35,36).…”
Section: Discussioncontrasting
confidence: 99%
“…Up to 60% of patients reported headaches but other studies found much lower rates (13%) . A causal link to GH was suggested as headaches improved dramatically in individual cases following successful surgery for acromegaly only to recur early with recurrent GH excess . Further support for a direct endocrine role of GH in the pathogenesis of headache derives from data on GH replacement in GH deficiency.…”
Section: Pathophysiology Of Headache In Pituitary Diseasementioning
confidence: 99%
“…4,51-55 A causal link to GH was suggested as headaches improved dramatically in individual cases following successful surgery for acromegaly only to recur early with recurrent GH excess. 56 Further support for a direct endocrine role of GH in the pathogenesis of headache derives from data on GH replacement in GH deficiency. In a large cohort of more than 30 000 children treated with GH for GHD, headache was reported with an incidence of 793Á5 of 100 000 patient years on initiation of therapy.…”
Section: Biochemical Aspectsmentioning
confidence: 99%
“…These patients reported a variety of types of headaches (Levy et al, 2005 ). Headaches improved dramatically in individual cases following successful surgery on removal of the tumor only to return with recurrent GH excess (Marzocchi et al, 2005 ). Additionally, somatostatin analogs rapidly eased headaches (Williams et al, 1987 ).…”
Section: Growth Hormonementioning
confidence: 99%